An obscure cause of gastrointestinal bleeding: Recurrent duodenal variceal hemorrhage treated with intramuscular octreotide in the absence of portal hypertension. Issue 1 (12th December 2022) - O'Neill, Robert S; Wang, William J; Chan, Patrick; Ho, Vincent; Verdon, Christine; Turner, Ian; Acharya, Priya
Abstract: Duodenal varices (DVs) are ectopic gastrointestinal varices (ECVs) associated with portal hypertension (PH). We present the case of an 82‐year‐old woman who presented with symptomatic anemia secondary to DV hemorrhage diagnosed on oesophagogastroduodenoscopy. This lesion was treated with endoscopic adrenaline injection and clip application. The patient re‐presented on multiple occasions with bleeding recurrence localized to the duodenum, which was managed with intramuscular octreotide and oral beta‐blockade resulting in sustained remission of bleeding. This case highlights a rare cause of upper gastrointestinal hemorrhage and highlights the value of somatostatin analogues for conservative treatment of DVs. Abstract : Duodenal varices are ectopic gastrointestinal varices associated with portal hypertension. This case highlights a rare cause of upper gastrointestinal hemorrhage in the absence of portal hypertension and highlights the value of somatostatin analogs for conservative treatment of duodenal varices.